The mortality of Caryocar brasiliense in northern Minas Gerais State, Brazil - doi: 10.4025/actasciagron.v34i2.13120 (Acta Scientiarum. Agronomy, 2011)
The purpose of this work was to study the percentage of healthy trees, living trees and healthy branches and the renewal (natural propagation) of Caryocar brasiliense associated with the properties of soil, the floristic diversity and the canopy size of this plant. Lower proportions of live C. brasiliense trees and of healthy branches were found in the Savanna of Ibiracatu, where only 30% of the trees were healthy and without visible signs of attack by wood borers and by Phomopsis sp. We observed that C. brasiliense trees in areas where the soils contained higher levels of summed chemical bases and total sand (fine + gross) were less healthy. Moreover, the areas whose soils contained higher levels of aluminum and clay had a higher percentage of healthy C. brasiliense trees and branches. Smaller percentages of live and healthy trees and healthy branches were noted in areas with higher floristic diversity. Overall, the higher mortality of C. brasiliense trees may be associated with a higher pH and a lower content of aluminum, silt and clay, with competition with other tree species for nutrients, water and light, with the attack of Cossidae and particularly with the attack of fungi, Phomopsis sp.